Semantic Systematization of Plant Vocabulary in Poetic Texts of Ivan Bunin - O. A. Selemeneva; N. A. Borodina (Научный диалог)
This article addresses the issue of Ivan Bunin's literary language, focusing particularly on the phytonymic tools employed in his poetic texts. The aim of the study is to systematize and describe the phytonymic lexicon found in the poetry of Bunin. The research material comprises lyrical texts (over 900 poems) included in a scholarly edition published in 2014, prepared by T. M. Dvinyatina. The author has compiled a database of examples featuring 237 plant nominations. The analysis employs descriptive, taxonomic, distributive, and statistical methods, as well as componential and contextual analysis techniques. Three principles have been identified that organize the plant names in Bunin's poetry into a coherent system: subordination of units, multi-layered structure, and the combination of polysemy and dichotomy in distinguishing taxa at different levels. It has been established that Bunin's poetry encompasses 22 semantic groups of plant names, varying in the number of designations within each group. The four most substantial groups are identified as follows: “Partitive Plant Names” (22.4% of the total corpus), “Names of Plant Communities” (12.7%), “Names of Non-Fruiting Deciduous Trees” (10.6%), and “Names of Ornamental Herbaceous Plants” (8.5%). Furthermore, it is demonstrated that alongside conventional units, Bunin's plant names also features individual-authorial formations.